Kritik Nalar Islam Indonesia: Tinjauan Problematis Relevansi Teks dan Konteks - Wildan Hidayat (Department of Ilmu al-Qur'an dan Tafsir, Faculty of Ushuluddin and Adab, State Islamic University of Sultan Maulana Hasanuddin Banten, Indonesia, 2019)
This paper specifically discussed about non-Muslim leadership in the Islam context, especially in Indonesia. This paper also discussed with the studiedconcepts of leadership in Islam (non-Muslim) and Islamic countries which are led by people with another religion (non-Islam). Not only to the extent ofpermissibility or non-indulgence of non-Muslim leadership in Islam, but it presented the opinions of the pros and cons of this case. Then it can be takena formulative idea that can bring Moslem of Indonesia to come up from the stagnancy of unknowledgeable sektesentric pattern against the rejection non-Muslim leadership without any real solution for himself and the Muslim community. Especially if the concept became contextualized with an Indonesiacountry with a Muslim as majority.